Importance of Toilet in Nuclear Medicine and Molecular Imaging Center - Ajay Kumar Yadav; Om Prakash Yadav; Birendra Yadav; Amardeep Chaudhary (Janaki Medical College Journal of Medical Science, 2025)
The practice of nuclear medicine imaging and radio-nuclide therapy involves administering a radioactive compound, which is labelled with a gamma ray or positron or beta minus emitting radionuclide into the body of patients resulting in radiation emissions from the patients until their radioactivity becomes negligible. These are used to provide diagnostic information in a wide range of disease states and they range from those with short half-lives such as 15O, 18F, 99mTc emitting photons whereas relatively long-lived ones such as 131I with both gamma ray and beta particle emitting for radio-nuclides therapy. Since the patients excrete much of the radiation via urination in the nuclear medicine facility, Special toilet (Hot or Active Toilet) for Nuclear Medicine patients is required. Because of the patients excrete much of the radiation via urination, patient toilet should not use for general patients, patient visitors and hospital staff.